Antibacterial Activity Test of Green Betel Leaf Extract (Piper betle Linn.) against Methicillin-Sensitive Staphylococcus aureus - Syifa Az Zahrah Manaf; Nurul Wiqoyah; Yuani Setiawati (Majalah Biomorfologi, 2025)
Highlights Green betel leaf extract, particularly cultivated in Batu City, can inhibit and kill MSSA. Green betel leaf extract, particularly cultivated in Batu City, can be developed into a new alternative treatment as an effective antibiotic to kill MSSA bacteria.   ABSTRACT Background: Asia is one of the regions with the highest prevalence rates of Staphylococcus aureus (S. aureus) infection. Green betel leaves (Piper betle Linn.) have been shown to possess antibacterial potential due to their active compound content. Objective: To investigate whether betel leaf extract affects methicillin-sensitive Staphylococcus aureus (MSSA). Material and Method: This research was a descriptive experimental study focusing on the antibacterial activity test of green betel leaf extract against MSSA. The MSSA bacteria used were bacterial preparations in the Microbiology Laboratory of the Faculty of Medicine, Universitas Airlangga. The green betel leaf extract was obtained in 2023 in Batu City, East Java, Indonesia. The antibacterial activity test technique used was the dilution test. The tool used in data processing was Microsoft Excel. Results: Germs were found in the dilution test, particularly in tubes with concentrations of 50 mg/mL. The study also highlighted that no growth of germs was found based on the results obtained for the increase of MSSA on agar plates at concentrations of 800 mg/mL, 600 mg/mL, 400 mg/mL, and 200 mg/mL. The study also found that the growth of MSSA germs was at 100 mg/mL and 50 mg/mL. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of green betel leaf extract against MSSA were 100 mg/mL and 200 mg/mL, respectively. Conclusion: The extract of green betel leaves, particularly cultivated in Batu City, East Java, Indonesia has been shown to possess antibacterial activity, which can inhibit and kill MSSA bacteria. Further research is needed on the antibacterial activity of green betel leaf extract against other bacterial species.